Influence of Professional Identity on the E-Learning Adaptability Among Chinese Nursing Students During COVID-19 - Wang, Huixiao; Yang, Mingying (Frontiers in Public Health, 2022)
Background The traditional face-to-face education methods have been altered to E-learning due to the outbreak, and the E-learning adaptability of nursing students will directly affect the effectiveness of online education. The professional identity of nursing students refers to the positive perception, evaluation, and emotional experience of the nursing profession and identity to be undertaken, which may affect the E-learning adaptability of nursing students during the coronavirus disease 2019 (COVID-19). This study aimed to explore the impact of professional identity on the E-learning adaptability of the Chinese nursing students during COVID-19. Methods This study was conducted in three medical schools in Yunnan Province, China from August to October 2020. Data collection consisted of three sections: participants' characteristics, learning adaptability, and professional identity. Results A total of 585 nursing students had a moderate level of E-learning adaptability. There was a positive correlation between E-learning adaptability and professional identity (r = 0.316 0.505, p < 0.001). In addition, the professional identity was associated with predictors of the E-learning adaptability among nursing students (p < 0.001). Conclusion There was a moderate level of E-learning adaptability among the Chinese nursing students during the COVID-19 crisis. Enhancing the professional identity is critical in improving the E-learning adaptability among nursing students.